2015
DOI: 10.1097/qco.0000000000000132
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis treatment in the presence of HIV

Abstract: Until a prospective, randomized study is conducted, inconsistency with treatment will continue. We offer a pragmatic approach to recognizing patients who may require further investigation or neuropenetrative antibiotic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…6,21 It is well known that patients with any levels of CD4 cell count could get infected by T pallidum , presumably, the CD4 cell counts was not related to the diagnosis of syphilis or neurosyphilis. 22 However, we were unable to explain the finding that CD4 <350 per μL was a predictor for neurosyphilis among all the co-infected patients with or without neurological symptoms. Therefore, we thought that the different composition of sample was the main reason for this discrepancy.…”
Section: Discussionmentioning
confidence: 70%
“…6,21 It is well known that patients with any levels of CD4 cell count could get infected by T pallidum , presumably, the CD4 cell counts was not related to the diagnosis of syphilis or neurosyphilis. 22 However, we were unable to explain the finding that CD4 <350 per μL was a predictor for neurosyphilis among all the co-infected patients with or without neurological symptoms. Therefore, we thought that the different composition of sample was the main reason for this discrepancy.…”
Section: Discussionmentioning
confidence: 70%
“…Thus unusual presentation of syphilis is possible in patients with PLHWA as observed in other studies. [5][6][7] Resistance to antimicrobial therapy at the standard dosage, requirement of higher dosage, resistance and relapse of infections were observed in the patients with PLWH. This is similar to the observations in the other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that treatment guidelines unanimously state that clinical management of HIV-infected patients does not differ, some providers use three dose BPG in HIV-infected patients for several reasons: 1) a higher risk of asymptomatic neurosyphilis, 2) reduced immune clearance of infection, and 3) higher serological failure compared to HIV-uninfected patients [60, 79]. In fact, a 2009 study found that 62% of American infectious disease clinicians would prescribe three doses of BPG to treat an HIV-infected patient with secondary syphilis, even though the recommendation only requires one dose [51].…”
Section: Clinical Managementmentioning
confidence: 99%
“…Although enhanced treatment can be rationalized, the evidence is lacking [80]. Experts have acknowledged that the available research on syphilis treatment among HIV-infected patients has been limited and primarily focused on serological outcomes [79, 81, 82]. Even though non-treponemal titers have been used to monitor syphilis response for decades, Tuddenham and Ghanem argue that serological titers may not correlate to clinical outcomes, especially for HIV-infected patients who can have persistently elevated non-treponemal levels unrelated to syphilis activity [83].…”
Section: Clinical Managementmentioning
confidence: 99%